THE ROLE OF ARTIFICIAL INTELLIGENCE IN MODERN TEACHING - Ruziev Bekhruz (TADQIQOTLAR, 2025)
Abstract:  The  emergence  of  artificial  intelligence  (AI)  in  education  is transforming  traditional  teaching  methods  by  introducing  intelligent  systems  that personalize learning, support teachers, and increase student engagement. This article explores how AI contributes to modern teaching through personalized content delivery, automated assessment, and intelligent tutoring systems. It also highlights the role of AI in  language  learning,  data-driven decision-making,  and  reducing  teacher  workload. While the benefits of AI are numerous, challenges such as data privacy, technological inequality,  and  the  importance  of  preserving  human  interaction  are  discussed.  The article  concludes  that  a  balanced  integration  of  AI  with  human-led  instruction  can enhance educational outcomes and create inclusive learning environments.